Widzieć siebie — z czasu minionego (Tamten Bolesława Leśmianai Kilkunastoletnia Wisławy Szymborskiej) - Głowiński, Michał (Poznańskie Studia Polonistyczne. Seria Literacka, 2009)
The article presents a juxtaposition of the following two brilliant poems Tamten (from the collection of poems entitled Napój cienisty, 1936) and Kilkunastoletnia (from the collection of poems entitled Tutaj, 2009) that employ the same idea of an encounter with oneself – an adolescent person (in the former poem) and a teenage girl (in the latter). The poems exceed the literary convention of just a lyrical reminiscence of the past, they rather form a particular dialogue with the narrator as he/she was years ago, or even propose a kind of a confrontation. Both poems indirectly feature reflections on the passing time and on the author’s identity. The poem written by Leśmian fits perfectly into his poetical system, both in terms of the introduction of metaphysical threads and the application of the elements of a love poem and in terms of the plot outline, somewhat reminiscent of his ballads. Szymborska’s poem also concurs with her own poetics mostly due to the characteristic subtle auto-irony.